Tiktok Live Streaming Thrifting: Strategi Mahasiswa di Bengkulu Untuk Meningkatkan Pendapatan di Era Digital - Heli Pera Mistika; Khairiah Elwardah; Yenti Sumarni (CV. ITTC INDONESIA, 2026)
This study examines the use of TikTok live streaming as a marketing medium in thrifting businesses operated by university students. The growing popularity of TikTok as a digital business platform provides opportunities for students to increase their income; however, not all entrepreneurs fully understand how to utilize this feature effectively. The purpose of this study is to analyze the role of TikTok Live in increasing students’ income and to identify supporting and inhibiting factors in its implementation. This research employs a qualitative method with a descriptive approach. Data were collected through in-depth interviews, observation, and documentation involving students who actively run thrifting businesses via TikTok Live. The results indicate that TikTok Live plays an effective role in increasing students’ income by expanding market reach, enabling direct interaction with consumers, and facilitating product promotion. Nevertheless, challenges such as time management, intense competition, and limited understanding of the TikTok algorithm remain obstacles for student entrepreneurs.